The preparation of a strategic plan on biodiversity management program : (Iklim Consult SDN. BHD., 1999)
University Malaysia Sabah (UMS) is planning to introduce a post graduate program on Biodiversity Management. The proposed program is being introduced by UMS in collaboration with a consortium of Danish university.